Atherogenic Index of Plasma Levels in Iraqi Diabetic and Diabetic Nephropathy Patients - Sulaiman M. Hasan (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study aimed todetermine the Levels of HbA1c %, urea, createnine, albumin,total cholesterol,triglyceride,high density lipoprotein (HDL-c), low density lipoprotein (LDL-C) and very low-densitylipoprotein (VLDL) in diabetic and diabetic nephropathy patients and to compare the results with that ofcontrol group. Then, to compare Atherogenic Index of Plasma levels in these groups that may be predictprone of patients to cardiovascular illness. This study has selected one hundred fifty participates who wereconsideredto be enrolled in this research with aged ranged (40-65) years that divided into three groups asfollows: group one (G1) consists of 50 healthy individuals as a control group, group two (G2) consists of50 patients with diabetes and group three (G3) consists of 50 patients with diabetes and nephropathy ascomplication.This study illustrated significant increased were found in Total Cholesterol and low-density Lipoprotein in G2comparing to G1, while there was highly significant increase in total cholesterol and low-density lipoproteinin G3 comparing to G2 and in G1. Results, also, revealed highly significant increase in triglyceride and verylow density in G2 and G3 comparing to G1. Data demonstrated highly significant decrease in high densitylipoprotein in G2 and G3 comparing to G1. Also, demonstrated highly significant increase in AtherogenicIndex levels in G2 and G3 comparing to G1, while no significant increased observed in G3 comparing to G2.Sothe study concluded that Atherogenic Index is elevated in diabetic and nephropathy diabetic patients whocould be used as a marker for predict cardiovascular disease in patients groups.